2021
DOI: 10.1002/anie.202014677
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Photoinduced Electron Transfer in POM‐Bodipy Hybrids by Controlling the Environment: Experiment and Theory

Abstract: The optical and electrochemical properties of a series of polyoxometalate (POM) oxoclusters decorated with two bodipy (boron‐dipyrromethene) light‐harvesting units were examined. Evaluated here in this polyanionic donor‐acceptor system is the effect of the solvent and associated counterions on the intramolecular photoinduced electron transfer. The results show that both solvents and counterions have a major impact upon the energy of the charge‐transfer state by modifying the solvation shell around the POMs. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Though the application of advanced analytical techniques for the characterisation of POM-based assemblies and nanomaterials will surely continue to improve, it is also worth highlighting that theoretical studies also remain a considerable challenge owing to the time-consuming calculations required for such large systems containing a large number of heavy atoms. 256 As an example, density functional theory simulations are usually limited to systems containing just 4 discrete POM clusters. The combination of DFT with molecular dynamics simulation methods is, however, particularly well-suited for investigating aggregation processes at the molecular level.…”
Section: Perspectivesmentioning
confidence: 99%
“…Though the application of advanced analytical techniques for the characterisation of POM-based assemblies and nanomaterials will surely continue to improve, it is also worth highlighting that theoretical studies also remain a considerable challenge owing to the time-consuming calculations required for such large systems containing a large number of heavy atoms. 256 As an example, density functional theory simulations are usually limited to systems containing just 4 discrete POM clusters. The combination of DFT with molecular dynamics simulation methods is, however, particularly well-suited for investigating aggregation processes at the molecular level.…”
Section: Perspectivesmentioning
confidence: 99%
“…The results showed that both solvents and counterions exhibited a major impact upon the energy of the charge-transfer state by modifying the solvation shell around the POMs. Moreover, the smaller counterion and slower charge recombination in a less polar solvent can lead to a significantly shorter charge separation time [69] .…”
Section: Photocatalysismentioning
confidence: 99%
“…[14] POMs are always connected with other materials through covalent or non-covalent interactions to achieve certain functionalities, such as tailoring electrochemical properties, for example. [15] Amongst them, electrostatic interactions provide a vast platform for the combination of the negatively charged POMs with diverse cationic species. [16] Discrete supramolecular frameworks consisting of explicit coordination sites as the constitutional units, possess rigorous structures and precise positive charges.…”
Section: Introductionmentioning
confidence: 99%